A Late Middle Kingdom Temple Bakery at South Abydos - Wegner, Josef.
Recent excavations have exposed the original bakery belonging to the mortuary temple of Senwosret III at South Abydos. Initially founded as a six-chambered building, the bakery was expanded in several phases to become a larger complex that housed a series of chambers dedicated primarily to large-volume hearth baking. Associated ceramics show that baking practices involved parallel use of rough-ware trays (aprt) and cylindrical bread molds (bDA). The bakery was linked by a walkway system with adjacent buildings also involved in the production and supply of offerings to the temple. One of the neighboring buildings appears to have been a companion brewery that was removed and replaced during a phase of alteration to the production area. The bakery and related structures are components of a larger shena or production zone that once extended nearly 300 meters along the edge of the Nile floodplain between the temple and town at the site of WAH-swt-¢akAwra-mAa-xrw-m-AbDw. Evidence from the bakery and neighboring structures shows that the layout of the shena was an extension of the urban plan of the town of Wah-Sut. Flanked by the main institutional buildings, the site was spatially organized around this multi-activity production zone which formed the site’s economic and industrial nucleus.